Modulating the expression and activity of the nuclear import protein, Karyopherin β1, in cancer cells - Carden, Sarah (Division of Medical Biochemistry and Structural Biology, 2017)
Cancer is primarily a disease of disordered gene expression; the dysregulation of thousands of different genes has been associated with the progression of many types of cancer. Previous research from our laboratory aimed at identifying genes differentially expressed in cervical cancer compared to normal patient tissue, found Karyopherin β1 (Kpnβ1), the primary nuclear import protein, to be significantly overexpressed in cervical cancer tissue. Further studies showed that inhibition of Kpnβ1 expression by siRNA resulted in cancer cell death, while non-cancer cells were only minimally affected. These results suggest that Kpnβ1 has potential as an anti-cancer therapeutic target, thus warranting further research into the association between Kpnβ1 expression and cancer progression. In this study, we investigated the biological effects associated with Kpnβ1 overexpression in order to further elucidate the relationship between Kpnβ1 and the cancer phenotype. Our data revealed that Kpnβ1 overexpression, above what was already detected in cancer cells, resulted in reduced proliferation and an associated delay in cell cycle progression. Additionally, overexpression of Kpnβ1 caused changes in the morphology and adhesion properties of cells. Co-expression of Ran, an important nuclear transport factor, binding partner and regulator of Kpnβ1, resulted in a further reduction in proliferation (greater than that of overexpression of either Kpnβ1 or Ran alone), suggesting that cells are particularly unable to handle an imbalance in the levels of Kpnβ1 and Ran. Previous work from our laboratory using a newly identified small molecule, Inhibitor of Nuclear Import-43 (INI-43), showed that INI-43 significantly reduced the proliferation of cancer cells of different tissue origins and interfered with the nuclear import function of Kpnβ1. In order to investigate the specificity of INI-43 for Kpnβ1 in this study, we performed experiments to determine whether overexpression of Kpnβ1 could rescue cancer cells from the negative effects associated with INI-43 treatment. Results revealed that stable overexpression of Kpnβ1 was able to rescue cell viability, as well as the inhibitory effects that INI-43 had on the nuclear import of Kpnβ1 cargoes NFκB p65 and NFAT. Kpnβ1 overexpression was also able to rescue cells from an INI-43 induced G2/M cell cycle block. In addition, treatment of cells with INI-43 enhanced the degradation of Kpnβ1, indicating that INI-43 is likely acting by targeting Kpnβ1. In order to determine the effects of Kpnβ1 dysregulation in HeLa cells, live cell time-lapse videomicroscopy was used to study cells as the progressed through the cell cycle. Inducible expression of Kpnβ1-EGFP, as well as the treatment of cells with the small molecule inhibitor INI-43, were used as mechanisms of dysregulation. Results revealed that modulation of Kpnβ1 by either overexpression or inhibition caused a disruption in mitotic progression, with the appearance of distinct mitotic abnormalities. The treatment of cells expressing Kpnβ1-EGFP with INI-43 resulted in a significant reduction in (or rescue of) the negative effects associated with either condition alone. Taken together, this data suggests that a precise balance of Kpnβ1 expression is required for the correct functioning of cancer cells; when the balance is perturbed in either direction (i.e. with overexpression of Kpnβ1 or INI-43-mediated inhibition of Kpnβ1) negative effects associated with a variety of biological processes are observed. In addition, results from rescue experiments conducted using Kpnβ1 overexpression in combination with INI-43 treatment suggest that that INI-43 is acting, at least in part, by targeting Kpnβ1.